Pedagogical Intentions in Lecturer–Student Classroom Discourse: A Speech Act Analysis of a Linguistics Course - Siska Oktawidya Wati; Sirajul Munir; Hafizul Chair; Azza Suzuasmisyah (Universitas Pahlawan Tuanku Tambusai, 2026)
This study investigates how speech acts are employed to construct pedagogical intentions in lecturer–student classroom discourse in Linguistics classes at UIN Mahmud Yunus Batusangkar, Indonesia. the study examines how classroom utterances function not only as linguistic expressions but also as pedagogical actions. A qualitative case study with pragmatic discourse analysis was conducted, involving three lecturers and 34 undergraduate students. Data were collected through non-participant observation, audio recordings of class sessions, field notes documenting non-verbal cues and classroom context, and semi-structured interviews with lecturers and students. A subset of 300 representative utterances was selected and analyzed based on Austin and Searle's frameworks. Frequency and percentage calculations were conducted to determine the distribution of speech act types. Trustworthiness was ensured through triangulation, peer debriefing, intercoder checking, and member clarification, while ethical approval was obtained and participants' identities were anonymized. Findings reveal that directive acts dominated classroom discourse (40%, n=120), followed by assertive acts (26.7%, n=80), expressive acts (16.7%, n=50), locutionary acts (10%, n=30), and commissive acts (6.7%, n=20). Seven pedagogical intentions were identified: instructing, motivating, clarifying, reinforcing, entertaining, evaluating, and concluding. This study demonstrates that speech acts function as integrated pedagogical resources enabling lecturers to manage classroom interaction, scaffold student understanding, and facilitate active participation. The findings contribute to pragmatics-informed pedagogy by providing empirical evidence from an Indonesian higher education context, an area previously underexplored in speech act research.